The effect of XPD/ERCC2 polymorphisms on gastric cancer risk among different ethnicities: a systematic review and meta-analysis. - Huiping Xue; Yan Lu; Bing Lin; Jinxian Chen; Feng Tang; Gang Huang (PLoS ONE, 2012)
Background Potential xeroderma pigmentosum group D (XPD), also called excision repair cross-complimentary group two (ERCC2), Lys751Gln and Asp312Asn polymorphisms have been implicated in gastric cancer risk among different ethnicities. Methods We aimed to explore the effect of XPD Lys751Gln and Asp312Asn polymorphisms on the susceptibility to gastric cancer among different ethnicities through a systematic review and meta-analysis. Each initially included article was scored for quality appraisal. Desirable data were extracted and registered into databases. 13 studies were ultimately eligible for the meta-analysis of Lys751Gln polymorphism and 9 studies for the meta-analysis of Asp312Asn polymorphism. We adopted the most probably appropriate genetic model (recessive model) for both Lys751Gln and Asp312Asn polymorphisms. Potential sources of heterogeneity were sought out via subgroup and sensitivity analyses, and publication biases were estimated. Results Statistically significant findings were apparently noted in Asians but not in Caucasians for both XPD Lys751Gln and XPD Asp312Asn polymorphisms. A statistically significant finding could be seen in noncardia-type gastric cancer for XPD Lys751Gln polymorphism. A statistically significant finding could also be seen in high quality subgroup, small-and-moderate sample size subgroup, articles published after 2007, or PCR-RFLP genotyping subgroup for XPD Asp312Asn polymorphism. Conclusions Our meta-analysis indicates that XPD Gln751Gln (CC) genotype and Asn312Asn (AA) genotype may seem to be more susceptible to gastric cancer in Asian populations but not in Caucasian populations, suggesting that the two genotypes may be important biomarkers of gastric cancer susceptibility for Asian populations, the assumption that needs to be further confirmed in well-designed studies among different ethnicities. Gln751Gln (CC) genotype may also be associated with noncardia-type gastric cancer risk, which should also be confirmed among different ethnicities in the future.